Optical and Thermal Investigations of Eutectic Metallomesogen Mixtures Based on Salicylaldiaminates Metal Complexes with a Large Nematic Stability Range - Hassan-Ali Hakemi; Valentina Roviello; Ugo Caruso (Inorganics, 2023)
The mesomorphic behavior and the miscibility properties of binary mixtures of a new series of Schiff base metallomesogen (MOM) are evaluated by differential scanning calorimetry (DSC) and polarized optical microscopy (POM). Nuclear magnetic resonance (NMR), elemental analysis (CHNX), Fourier-transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA) were used to certify the molecular structure of the compounds. The results revealed that the studied mixtures are completely miscible throughout the composition field and exhibit a nematic phase which covered the whole composition range. In the mixtures, the stability of the nematic phase varies continuously, and it is possible to highlight the presence of a eutectic composition with a wide mesogenic stability range.